Adult and Developing Zebrafish as Suitable Models for Cardiac Electrophysiology and Pathology in Research and Industry - Echeazarra, Leyre; Hortigón-Vinagre, Maria Pura; Casis, Oscar; Gallego, Mónica (Frontiers in Physiology, 2021)
The electrophysiological behaviour of the zebrafish heart is very similar to that of the human heart. In fact, most of the genes that codify the channels and regulatory proteins required for human cardiac function have their orthologs in the zebrafish. The high fecundity, small size and easy handling makes zebrafish embryo an interesting candidate to perform whole animal experiments within a plate, offering a reliable and low-cost alternative to replace rodents, and larger mammalian models in the study of cardiac physiology and pathology. The employment of zebrafish embryo has widen from basic science to industry, being of particular interest for pharmacology studies, since zebrafish embryo is able to recapitulate a complete and integrated view of cardiac physiology, missed in cell culture. As in the human heart, IKr is the dominant repolarizing current and it is functional as early as 48 hours post fertilisation. Finally, genome editing techniques such as CRISPR/Cas9 facilitate the humanization of zebrafish embryo by replacing zebrafish genes by its human orthologs, making humanized zebrafish embryo the most promising “human-like” in vitro model, since it allows the recreation of organ-like environment, which is especially necessary in cardiac studies due to the implication of dynamic factors, electrical communication and the paracrine signals in cardiac function.